Reading and Writing Patronio's Doctrine in Real Academia Española MS 15. - Burgoyne, Jonathan (Hispanic Review)
Studies the manuscript 15 of the Real Academia Española in Madrid (RAE 15). Organizing principles of RAE 15; Information on the exempla collection; Prologue reproduced by Richard Kinkade in his edition of "Los Lucidarios españioles."